The impact and transformation evaluation of art intervention in public space on ancient villages: a case study of Tengchong, Yunnan Province - Pengjun Wu; Xiaowen Li; YaFang Feng; Yao Liu (Scientific Reports)
Abstract As the need for balancing cultural heritage preservation with economic development becomes increasingly urgent, the sustainable development of ancient villages has emerged as a critical issue. This study focuses on the ancient villages of Tengchong, Yunnan, to examine the profound impact of art intervention in public spaces on their development. Through literature review, QGIS analysis, questionnaire surveys, and hierarchical analysis, the study reveals that art intervention plays a pivotal role in enhancing the environmental appearance (0.307), social and cultural values (0.270), village transformation (0.242), and economic benefits (0.181) of these villages. Art intervention not only significantly improves infrastructure and optimizes transportation but also effectively protects natural landscapes and environmental sanitation, fostering sustainable economic growth. By reasonably controlling costs, art intervention provides an innovative and feasible pathway for balancing cultural preservation with economic development, highlighting its unique value in promoting the sustainable development of ancient villages.